ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN BERAS PADA PABRIK PENGGILINGAN SUMBER GEDE - Vonny Tiara Narundana; Krisnawati Anggrayani; Agung Rachmadi (Jurnal Manajemen dan Bisnis, 2021)
Sumber Gede Milling Factory is a milling factory engaged in the roasting industry which produces rice which has problems due to a decline in sales due to inaccurate marketing strategies. The research objective was to determine the right marketing strategy to increase sales of Sari Buah and Bakal Buah rice products based on SWOT and BCG automatic analysis.This type of research is descriptive qualitative, the analysis used to analyze the problem is the SWOT analysis and the BGC matrix.The result of the combination of the SWOT matrix that has an effect is the SO and ST strategies that can be applied to increase sales.Based on the results of BCG analysis, the value of the market growth rate is 0.186%, while the results of the calculation of the relative market share are 1.29% or 0.0129%. The calculation results show that the Sumber Gede Mill is in the first quardan, namely the Question Mark area, the quard and I part which has a relatively low market share position, but has a high market share growth rate.